COMBINATORY WAYS OF COINING EUPHEMISMS - V.B. Velykoroda (Vasyl Stefanyk Precarpathian National University, 2015)
The article analyses the most productive combinatory ways of coining euphemisms in the English language. The provided models are illustrated with numerous examples, and the findings suggest that combinatory ways of word formation are characteristic of 20.5% of all euphemisms.